Occurrence of faecal endoparasites in reindeer (Rangifer tarandus) in two grazing areas in northern Norway - Lene Idland; Amalie Moen Juul; Ellen Karin Solevåg; Kristoffer Relling Tysnes; Lucy Jane Robertson; Kjersti Selstad Utaaker (Acta Veterinaria Scandinavica, 2021)
Abstract Background Semi-domesticated reindeer represent an important livestock industry and livelihood for a proportion of the human population in northern Fennoscandia. Reindeer husbandry is considered an extensive animal husbandry, where the animals are kept mostly on natural pastures, although sometimes kept in fenced areas for shorter periods. These reindeer may harbour a variety of parasites that may affect animal health and production. The relatively limited close contact between herds and owners gives limited opportunities for diagnosis and treatment of diseases in general. Furthermore, the effects of subclinical parasitism in livestock are commonly expressed as a reduction in productivity rather than clinical disease and mortality. Thus, specific knowledge of endoparasites and parasitic infections in these herds is scarce. This study investigated the occurrence of various endoparasites in reindeer by analysis of a total of 114 faecal samples from winter-slaughtered reindeer from two different grazing areas in Troms and Finnmark, Norway. Results Using a McMaster method, a Baermann technique, and a direct immunofluorescent antibody test, the following parasites were identified in the faecal samples with the occurrence data given as percentages: Strongylid eggs (62%), Nematodirinae spp. eggs (24%), Capillaria sp. eggs (42%) and Moniezia spp. eggs (17%), Dictyocaulus spp. larvae (14%) protostrongylid larvae (40%), Eimera spp. oocysts (23%), and Giardia duodenalis cysts (5%). Cryptosporidium oocysts were not detected. Parasite eggs, oocysts, and cysts were quantified. Molecular analysis revealed G. duodenalis sub-assemblage AI, a potentially zoonotic genotype not previously reported in reindeer from this region. Morphological analyses of Eimeria oocysts identified two species, Eimeria mayeri and Eimeria rangiferis, and molecular analyses of the cytochrome C oxidase I (coi) gene and 18 s rRNA (18SSU) gene of Eimeria confirmed the presence of Eimeria species that are specific to reindeer. Conclusions A high ...